Associations of demographics, aggravating factors, comorbidities, and treatments with atopic dermatitis severity in China: A national cross-sectional study - Jiahui Zhao; Zhixin Zhang; Hongguang Chen; Xia Dou; Zuotao Zhao; Lingling Liu; Yang Wang; Hang Li; Yuanyuan Ji (Chinese Medical Journal)
Abstract. Background:. Atopic dermatitis (AD) is a chronic inflammatory skin disorder impacting populations worldwide, although its clinical characteristics and patient demographics remain uncharacterized in China. The aim of this study was to investigate the demographics, comorbidities, aggravating factors, and treatments in AD patients across different age groups in China. Methods:. This cross-sectional study included Chinese AD patients from 205 hospitals spanning 30 provinces. Patients completed dermatologist-led surveys of general medical history, comorbidities, AD-related aggravating factors, and medications. Two-level mixed-ordered logistic regression was used to evaluate aggravating factors. Results:. Overall, 16,838 respondents were included in the final analysis (aged 30.9 ± 24.1 years). The proportion of severe AD was the highest in patients with AD onset at ≥60 years (26.73%). Allergic rhinitis and hypertension were the most common atopic and metabolism-related non-atopic comorbidities, respectively. AD severity was significantly associated with chronic urticaria, food allergies, and diabetes. Aggravating factors including foods, seasonal changes, and psychological factors were also linked to AD severity. The cross-sectional survey implied that severe AD may be related to the undertreatment of effective systemic or topical interventions. Conclusion:. To enhance the management of AD, it is crucial to consider both aggravating factors and the increased utilization of systemic immunotherapy. Registration:. ClinicalTrials.gov, NCT05316805